HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR IPS SISWA KELAS V SDN 3 WRINGIN ANOM TAHUN PELAJARAN 2017/2018 - Abu Rizal Bahri; Heldie Bramantha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
Learning social science in 5th grade has a many materials, so that students in 5th grade students SDN 3 Wringin Anom have different levels of motivasion, which affects the acquision of different learning outcomes. The problem formulation in this research was whether there was a relationship between motivation with sosial science learning outcomes of the 5th grade SDN 3 Wringin Anom academic year 2017/2018?. This study aimed to determine the relationship between motivation with sosial science learning outcomes of the 5th grade students SDN 3 Wringin Anom academic year 2017/2018. The type of this research was correlational research. The population of this research was students in 3 Elementary School Wringin Anom. This research was used purpusive sampling technique, with the number of samples is fifteen students. This reaserch consist of independent variables and dependent variables, the independent variables that is motivation (X), and dependent variables that was sosial science learning outcomes (Y). The data collection techniques used in this research was using questonnaires and documentation. The result showed that the relationship of motivation with sosial science learning outcomes of the 5th grade was in strong category, the corelation coefficient is 0,733 > r table 0, 514 calculation using product moment correlation analysis. Based on the explanation be concluded that between motivasion with sosial science learning outcomes there was relationship with strong category. Suggestions for should help students improve their motivation. For students, it was better to increase the motivation to learn, and for the school should always create a learning process that could improve learning motivation